METODE PENYULUHAN PADI PADA PROGRAM UPAYA KHUSUS PENINGKATAN PRODUKSI PADI DI JAWA TENGAH - Nur Fitriana (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2020)
Implementation of rice extension as an effort to support the Program Upaya Khusus Peningkatan Produksi Padi, Jagung dan Kedelai (Upsus Pajale) in Central Java Province. The extension of Integrated Crop Management (IPM) of rice technology aims to encourage farmers to implement the technology. The selection of extension methods affects farmers' acceptance of the IPM of rice. This study aims to examine the methods and media of extension used to disseminate IPM of rice and how farmers respond to extension methods and extension media. This study uses a quantitative approach. Data collection using survey techniques from September 2018 to March 2019. Respondents from 153 farmers were in 6 districts / cities, Purbalingga Regency, Tegal Regency, Magelang Regency, Purworejo Regency, Magelang City and Semarang City. The results showed that during the program period, extension worker used a variety of extension methods. Based on the target number, the extension worker used two extension methods, namely the group approach and the individual approach. Based on the recipient's senses, the extension worker used methods that prioritize the sense of sight, sense of hearing and a combination of sense of acceptance. The type of communication used is direct and indirect communication using print media, electronic media, and sometimes social media. Farmers think the extension method, extension media and extension tools are good enough. The response of farmers who rate is good enough can be an indicator that the implementation of extension is going well enough. For the implementation of extension services in the future, it is recommended that extension agents choose extension methods that are more appropriate for farmers so that the extension goals are achieved optimally.